Тетралогія В. Малика «Таємний посол» та роман Г. Сенкевича «Вогнем і мечем»: типологічне порівняння - Шаповалова, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
The novels by V Malyk and G. Senkevsch have much in common although written with a different purpose and for audiences not alike. There is a considerable similarity in the system of characters, the motives of adventurous kind used in the plot construction, the principles of work with historical material and the language frame. Most of the similarities mentioned are explained by the fact that the novels by Sir Walter Scott served as a pattern for both authors. Thus the trilogy «Secret Ambassador» can be regarded not only as a book for entertainment, but also as a valuable literary work in Polish and English literature.